Indonesian Society in Climate Change Adaptation Participation: A Literature Review - Widyanarko, Unggul; Puspitasari, Diana (Amcolabora, 2026)
Climate change poses serious threats to Indonesia, particularly at the local level where it affects both livelihoods and ecosystems. Strengthening community participation has become a central strategy for enhancing social and ecological resilience, and recent government regulations emphasize its importance. Yet, the effectiveness of such participation remains uneven and requires further examination. This study conducts a systematic literature review of 26 Scopus-indexed articles using the keywords “community participation,” “climate change adaptation,” and “Indonesia.” The review explores publication trends, dominant themes, development approaches, key actors, and factors influencing participation. Findings indicate that participation is generally collaborative and context-specific, with community-based adaptation emerging as the dominant model. Communities contribute positively to resilience by strengthening local capacity, building adaptive infrastructure, and enhancing social cohesion. However, participation is shaped by enabling and constraining factors, including institutional support, local facilitation, and alignment with socio-cultural contexts. Overall, the study highlights the crucial role of communities not only as program beneficiaries but also as active agents in sustainable climate adaptation. Strengthening institutional frameworks and ensuring locally grounded approaches are essential to maximize the effectiveness of community participation in addressing climate challenges in Indonesia.